Deciphering the impact of rpoB mutations on the gene expression profile of Mycobacterium tuberculosis - Du Plessis, Juanelle (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.